Lower Expression of miR-26a in PBMCs Indicates the Occurrence of Early-Onset Neonatal Sepsis and Is Partly Mediated by the Upregulation of PTEN - Zhao, Ziyan; Zhang, Jiajie (Frontiers in Pediatrics, 2021)
Aim It is difficult to identify neonatal sepsis early due to the lack of specific markers. The aim of the present study was to explore whether miR-26a expression in PBMCs could be used as a diagnostic marker of the disease and whether PTEN was involved in suppressing miR-26a expression. Methods A total of 51 early-onset septic newborns and 102 healthy newborns were included. Blood specimens were collected from the septic newborns at the time of clinical diagnosis (baseline) and again between 72 and 96 hours after birth. Blood specimens were collected from the healthy newborns on admission. The expression of miR-26a and PTEN in the PBMCs was measured using RT-qPCR. Other data, including hemoculture, were collected from the medical records. Results In septic newborns with and without a positive hemoculture, a lower baseline level of miR-26a in PBMCs was associated with a higher risk of disease. Additionally, at baseline, there was a certain linear relationship between the levels of miR-26a and two serological inflammatory markers (i.e., white blood cell count and C-reactive protein level) in septic newborns. In addition, the baseline expression of miR-26a and PTEN showed a reverse linear relationship. Compared with the baseline, the expression of miR-26a was higher and the expression of PTEN was lower in septic newborns starting at 72 hours after birth. Conclusion Lower baseline miR-26a expression in PBMCs indicated the occurrence of early-onset neonatal sepsis, and reduced miR-26a expression might be partly related to the inflammatory process and PTEN upregulation.